Almost One-Third of Large Sessile Serrated Polyps Are Missed on CT Colonography - Singla, Manish; Kemp, Jean D; Goldberg, Michael E; Cirigliano, Vito V; Bobele, Gilda M; Veerappan, Ganesh R; Young, Patrick E (Turkish Journal of Gastroenterology, 2021)
Background: Nearly one-third of colorectal cancers (CRC) arise via the serrated pathway. CT colonography (CTC) is a CRC screeningexamination. Endoscopic detection of sessile serrated polyps (SSPs) varies widely; it is unknown whether CTC effectively detects SSPs.The aim of this study is to determine whether CTC detects SSPs at an institution that performs a large volume of CTC.Methods: We conducted a search of pathology records to identify serrated polyps (SPs) from 2005 to 2012. We extracted demographicdata from the electronic health records (EHRs) of subjects with an SSP and examined endoscopy reports for location and size of eachSSP. We identified subjects with a CTC within 1 year prior to the colonoscopy that found an SSP, and determined if the CTC identifiedthe SSP.Results: Our search found 3978 subjects with SP over the 7-year period. Seven hundred thirty-two subjects had at least 1 SSP. Eightytwosubjects had CTC done within 1 year prior to the colonoscopy that identified SSP. Seventy-nine subjects’ polyps were identified onCTC. CT colonography was done an average of 38 ± 54 days prior to colonoscopy. One hundred fifteen SSPs were identified endoscopically.A total of 48.7% of all SSPs were identified via CTC; larger SSPs were more likely to be seen on CTC (P < .001), and 69.6% of SSPslarger than 10 mm were found via CTC. Proximal SSPs were more often identified than distal SSPs (P = .005).Conclusion: Given the miss rate for SSPs on CTC, endoscopists should be vigilant about examining the proximal colon in subjectsreferred after CTC, even if the imaging does not reveal a proximal polyp.